Challenges of software developers: the Namibian Government experience. (2018) - Nehemia-Maletzky, Monica; Iyamu, Tiko
Almost 15 years after the National Development Program (NDP) was initiated, the Namibian Government continue to outsource most of its software development to companies from other countries. This is considered by the general populace of the country to have a negative impact on the economy, as well as skill and knowledge transfer. This research, through multiple case studies, examined and discusses the impact of lack of in-house software development experts in the country. From the empirical study, a framework for software development skill (FSDS) was developed. The framework consists of factors which include strategic objectives of the government, strategic objectives of the IT divisions, policy and standards, IT management support and skills and development. The primary aim of the FSDS is to assist the Namibian Government institutions to understand the influencing factors, in building software development capacity in the country.